The Relationship between Learning Styles and Learning Outcomes of Class VII Students at SMPN 42 Padang - Tussadiyah, Alimah; Anugrah, Septriyan; Pratiwi, Rahmi; Kurnia, Reni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The teacher's teaching style must be in accordance with the student's learning style. This is the same as the teacher's teaching style, which is the learning style of Chatib students, (2016). If teachers and educators already know the learning style that each individual has in the classroom, then this will help teachers in determining a good and more effective learning plan. Based on the results of the pre-observation conducted by the author, information was obtained that there were several students who during learning focused on the learning process given by the teacher. Other students who were mainly in the back position were lazy. In addition, there are students who like to disturb their friends to study. This observation shows the difference in learning styles of the students. This research is a type of correlational descriptive quantitative research. The population used in this study is 131 students registered in the 2024/2025 school year with a sample of 98 students selected using the Simple Random Sampling technique. Data collection in this study uses a learning style questionnaire and report card scores for learning outcomes. The data was processed using percentage analysis techniques and to test the relationship of the analysis data using the Pearson product moment formula. The results of the study found that in general, the learning style of SMPN 42 Padang students is in the sufficient category. Then, the learning outcomes of SMPN 42 Padang students are in the poor category. After conducting a correlation test analysis using the SPSS program, the results showed that there was a positive relationship between learning style and learning outcomes of SMP 42 Padang students with a correlation coefficient value of X and Y variables of 0.227 with a level of 0.024 with a total of 98 students.